Overview of Learning of Physical Education With The Locomotive Ability of Children With Special Needs In SLB-B At SLB Negeri Pembina Cimalaka - Fitri, Shafira Nabila; Alifah, Meilani Anindita; Firmansyah, Restu Dwi; Rusnindar, Dera; Syarif, Muhammad Fatiar; Fauzi, Rizal Ahmad (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
Children with special needs who are deaf are children who have hearing problems. Children with special needs who are deaf will certainly face various problems with their special needs. All these problems need to be resolved by providing education, guidance, and training services so that problems that arise can be resolved well. This research aims to determine the level of locomotor ability in children with special needs in SLB-B at the Pembina Cimalaka Sumedang State SLB school. This type of research is descriptive research with several research subjects, namely students with hearing impairment, totaling 20 SLB-B students at the Pembina Cimalaka Sumedang State SLB school.